Ductile and intergranular brittle fracture in a two-step quenching and partitioning steel. (December 2018) - Xiong, Zhiping; Jacques, Pascal J.; Perlade, Astrid; Pardoen, Thomas
Abstract: A two-step quenching and partitioning steel exhibits ductile fracture under uniaxial tension and unexpectedly intergranular brittle fracture in the case of pre-cracked configuration. A gradual retained austenite-to-martensite transformation because of low stress triaxiality under uniaxial tension, leads to ductile fracture with voids formation between fresh and tempered martensite resulting from the large strain partitioning and localization. When the retained austenite fast transforms to martensite in the near crack tip region because of high stress triaxiality, intergranular fracture is promoted by the high maximum principal stress level and by the formation of brittle martensite necklace along tempered martensitic packet boundaries. Graphical abstract: Unlabelled Image